2017
DOI: 10.1016/j.jtho.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of ALK -Positive Non–Small Cell Lung Cancer (NSCLC) Patients with De Novo EGFR or KRAS Co-Mutations Receiving Tyrosine Kinase Inhibitors (TKIs)

Abstract: De novo concurrent ALK/KRAS co-alterations were associated with resistance to ALK TKI treatment in seven out of eight patients. In patients with ALK/EGFR co-alterations, outcomes with ALK and EGFR TKIs seem inferior to what would be expected in patients with either alteration alone, but further studies are needed to clarify which patients with ALK/EGFR co-alterations may still benefit from the respective TKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…ALK rearrangements have generally been reported to be mutually exclusive with other driver alterations in NSCLC such as EGFR and KRAS mutations, although few studies have shown that they can coexist [30][31][32]. We found KRAS mutations in three of the examined patients, which likely represented different tumor clones, indicative of the heterogenous nature of lung cancer.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…ALK rearrangements have generally been reported to be mutually exclusive with other driver alterations in NSCLC such as EGFR and KRAS mutations, although few studies have shown that they can coexist [30][31][32]. We found KRAS mutations in three of the examined patients, which likely represented different tumor clones, indicative of the heterogenous nature of lung cancer.…”
Section: Discussionmentioning
confidence: 55%
“…However, the KRAS mutation was found at an AF of 79% in the diagnostic biopsy taken 5 years earlier in connection with curative-intended stereotactic treatment (Table S3). Thus, KRAS mutations and ALK rearrangements can coexist, and, interestingly, the three patients with this genomic profile had response or stable disease at their first evaluation following ALK TKI start [32].…”
Section: Discussionmentioning
confidence: 96%
“…30 Recently, however, some cases of NSCLC with coalteration have been reported in the literature, [38][39][40][41] and these coaltered patients may benefit from treatment with more than one targeted drug. 42 There were 33 cases (3.7%) with coalteration in our study, including EGFR/PIK3CA (2.1%, 19 cases), EGFR/HER2 (0.7%, six cases), HER2/KRAS (0.3%, three cases), EGFR/KRAS (0.1%, one case), EGFR/ ROS1 (0.1%, one case), EGFR/NRAS (0.1%, one case), KRAS/PIK3CA (0.1%, one case), and a triple KRAS/ PIK3CA/HER2 (0.1%, one case) coalteration. Previous studies revealed that KRAS, BRAF, and PIK3CA mutation have been related to efficacy of EGFR-TKI, metastasis or overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant driver gene mutations in EGFR and ALK have been detected in 1.3%‐15.4% of the patients with non‐small cell lung cancer (NSCLC), depending on the method used . Among the patients harboring EGFR / ALK coalterations, some responded to treatment with an EGFR‐TKI (ie, gefitinib, erlotinib, icotinib, or afatinib), while others responded to treatment with an ALK‐TKI (crizotinib) or both . To the best of our knowledge, there is currently no consensus for the optimal management for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…KRAS proto‐oncogene ( KRAS ) and B‐Raf proto‐oncogene ( BRAF ) have been frequently studied in NSCLC, and mutation testing for these genes is recommended in the National Comprehensive Cancer Network guidelines for NSCLC KRAS mutations have been found more frequently in non‐Asian patients and former or current smokers and have been associated with mucinous adenocarcinoma . Furthermore, evidence suggested that KRAS mutations combined with EGFR mutations or ALK rearrangements could negatively impact the effects of TKI therapy . Meanwhile, the BRAF V600E mutation has been reported to be mutually exclusive with EGFR and KRAS mutations but has been found to co‐occur with other driver gene mutations …”
Section: Introductionmentioning
confidence: 99%